Motivação no funcionalismo público federal: um estudo exploratório na universidade federal do Amapá - unifap - (:unkn) unknown (UNIFAP - Universidade Federal do Amapá, 2017)
Currently, motivation has been gaining space when related to the organizational environment. In view of the influence and the impacts that it can cause on human behavior. In this sense, this paper aims to draw an exploratory look at the identification of the motivational profile of technical servers of the Pro-Rectorates of the Federal University of Amapá - UNIFAP. To support the article, the research has as theoretical reference the theories of Maslow (Hierarchy of Human Needs) and Herzberg (Two Factor Theory), in addition to the contribution of authors such as Chiavenato, Drucker, Marras and Bergamini. In this context, the data were collected through a questionnaire of 13 statements based on Herzberg's Theory, which analyzed the motivational and hygienic factors. The hygienic factors are related to the physical conditions and the work environment, and the motivational factors are intrinsic, consisting of the individual's achievement.
Keywords: Motivação; Teoria motivacional; Satisfação; CNPQ::CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO PUBLICA